PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING DAN KEPERCAYAAN MATEMATIKA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMPN 1 KUTA UTARA - Ni Luh Sintya Dewi (LPPM Universitas Bina Bangsa, 2023)
The problem that we often find in class is that students are less focused on learning mathematics, where teachers teach using conventional learning models. Students act as followers and passive recipients of the activities carried out. Therefore, it is necessary to apply a learning model that involves students in the teaching and learning process, so that they can develop the potential of each student independently. One of them is the problem posing learning model. The problem posing learning model is a learning model that requires students to compose their own questions or solve a problem. The purpose of this research is to find out whether there are differences in the mathematics learning outcomes of students who follow the problem posing learning model, whether there is an interaction effect between the application of the problem posing learning model and the belief in mathematics on learning outcomes, whether there are differences in learning outcomes between students who follow the problem posing learning model and students who follow conventional learning models in groups of students who have high mathematical confidence and low mathematical confidence. The results of hypothesis testing using two-way ANOVA. Based on the results of the research and data analysis, it was found that 1) there were differences in the learning outcomes of students who took the problem posing learning model and those who followed the conventional learning model. 2) There is an interaction effect between the application of problem posing learning models and mathematical beliefs on learning outcomes. 3) There are differences in the learning outcomes of students who follow the problem posing learning model with students who follow conventional learning models in groups of students who have high mathematical confidence. 4) There is no difference in the learning outcomes of students who follow the problem posing learning model with students who follow the conventional learning model in groups of students who have low mathematical confidence.